2013
DOI: 10.1063/1.4825245
|View full text |Cite
|
Sign up to set email alerts
|

Laser-seeded modulation instability in a proton driver plasma wakefield accelerator

Abstract: A new method for initiating the modulation instability (MI) of a proton beam in a proton driver plasma wakefield accelerator using a short laser pulse preceding the beam is presented. A diffracting laser pulse is used to produce a plasma wave that provides a seeding modulation of the proton bunch with the period equal to that of the plasma wave. Using the envelope description of the proton beam, this method of seeding the MI is analytically compared with the earlier suggested seeding technique that involves an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…[10][11][12][13][14] The SMI works properly only if a selected instability mode is somehow externally seeded. 2,[15][16][17] Otherwise, non-axisymmetric perturbations (hosing modes) belonging to the same instability family 18 could develop and destroy the beam. Even the axisymmetric modes are sufficient to destroy the beam, if several of them grow concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] The SMI works properly only if a selected instability mode is somehow externally seeded. 2,[15][16][17] Otherwise, non-axisymmetric perturbations (hosing modes) belonging to the same instability family 18 could develop and destroy the beam. Even the axisymmetric modes are sufficient to destroy the beam, if several of them grow concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…A short electron bunch [42], a powerful laser pulse [43], a sharp cut in the bunch current profile [40,44], or a relativistic ionization front copropagating within the drive bunch can seed the SMI quite well. Analytical and numerical calculations, however, have shown that bunches with long rise times (longer than or about the plasma wavelength) do not produce stable bunch trains [30,38,39].…”
Section: The Self-modulation Instabilitymentioning
confidence: 99%
“…[26]. Various options are possible for the seed perturbation: a short electron bunch [26], a powerful laser pulse [27], a sharp cut in the bunch current profile [18], or a relativistic ionization front co-propagating with the drive bunch [28]. Currently, the co-propagating relativistic front is considered as the mainstream variant, as this solution is chosen for AWAKE experiment.…”
Section: Introductionmentioning
confidence: 99%